Исследование процессов перестройки молекулярной структуры мацералов угля при температурной динамике - Бурчак, А.В.; Балалаев, А.К.; Сериков, Ю.А. (Геотехническая механика, 2012)
Проведено дослідження поведінки структури петрографічних мікрокомпонентів вугілля при низькотемпературному нагріванні. Показано, що методи ЕПР та ІЧ-Фур’є спектроскопії оцінюють фізико-хімічні ефекти різної природи. Для вітрініта встановлено зниження інтенсивності коливань вільних гідроксильних груп при одночасній активізації метилових та метиленових груп. Зареєстрована акумуляція енергії у спряжених системах інертініту. Investigations of the behavior of the structure of petrographic constituents in low-temperature heating were conducted. It is shown that the methods of EPR and FTIR spectroscopy estimate the physical and chemical effects of different origin. It was set the intensity of vibration of free 59 hydroxyl groups to reduce the vitrinite in the simultaneous activation of methyl and methylene groups. It was registered the accumulation of energy in conjugated systems of inertinite.